Impact of Sector and Region on Survival and Closure - Kar, Brajaballav; Das, Piyusa Pritiparnna (Indian Journal of Finance, 2022)
The objective of the study was to explore the mortality of companies across sectors and regions in India. Using a public dataset available from the Ministry of Corporate Affairs of India, we explored the survival and closure age distribution of Indian companies, specifically the variation of closure across different sectors and regions. First, the study found that the age distribution of companies’ surviving and closed had no significant difference. Secondly, the closure age distributions of different sectors and regions had significant differences. The number of companies and the span of ages is sufficiently large to claim the generalizability of the findings for India. The article contributes to the literature by extending the industry life cycle theory.